The Use of Sofosbuvir (SOF)-containing Direct Antiviral Agents (DAA)-based Regimens Requires Increase in Tacrolimus (Tac) Doses in Kidney Transplant (KT) Recipients with Hepatitis C Virus (HCV) Infection. (July 2018) - Polanco, Natalia; Fernández, Mario; García, Ana; Muñoz, Raquel; Trujillo, Hernando; Sevillano, Ángel; González, Esther; Aguado, José María; Praga, Manuel; Andrés, Amado
Abstract : Background: In contrast to DAA combinations that include NS3-4A protease inhibitors, the use of SOF-containing regimens based on NS5A inhibitors has not been shown to modify Tac levels after liver transplantation. Specific data on KT recipients are still lacking. Methods: We prospectively analyzed all the KT recipients that received SOF-containing DAA-based therapy in our center between November 2014 and November 2015. The primary end-point was sustained virologic response at 12 weeks after end of treatment (EOT) (SVR12). Therapeutic drug monitoring (TDM) for Tac and mofetil mycophenolate (MMF) was performed in whole blood samples at baseline (pre-treatment) and at weeks 2, 4, 8, 12 and 24. Dose adjustments were made as required while on therapy to maintain trough levels of immunosuppressive drugs within pre-treatment ranges. Results: We included 33 patients (mean age: 55.3 ± 10.3 years) with a median interval since KT of 8.5 years. Immunosuppression included Tac (100.0%), MMF (75.8%), prednisone (72.7%) and everolimus (6.1%). The DAA combinations used were SOF plus ledipasvir (90.9% [n = 30]) or daclatasvir (9.1% [n = 3]). Ribavirin was co-administered in 57.8% (n = 19) of patients. The intended duration of therapy was 12 (75.8%) and 24 weeks (24.2%), and 14 patients (42.4%) had completed the entire course at the time of analysis. The rates of undetectable HCV-RNA at EOT and SVR12 were 100.0% (14/14) and 100.0% (11/11), respectively. There were no significant differences in Tac (P-value = 0.911) or MMF levels (P-value = 0.785) between baseline and EOT (Table). However, Tac doses had to be increased in 92.8% (13/14) of patients by a median of 66.0%. Mean Tac daily doses at baseline and EOT were 2.6 ± 2.0 and 3.4 ± 1.4 mg, respectively (P-value <0.001). No further adjustments after EOT were required. MMF or everolimus doses were not modified. There were no episodes of acute rejection or other relevant adverse events. Conclusion: The use of protease inhibitors-free, SOF-containing regimens in KT recipients requires close TDM of Tac. The underlying mechanism might be related to improvement in hepatic function and Tac clearance rather than to direct drug-to-drug interaction.